Inuusinni Aqqusaaqtara – My Journey: Meeting the Information Needs of Inuit Living with Cancer - Ashton, Savanah; Torchetti, Tracy (Engaged Scholar Journal, 2020)
The Inuit Cancer Project aims to help Inuit better understand cancer and improve communication between Inuit with cancer and non-Inuit healthcare providers and support services. The project has created resources that are culturally relevant, appropriate, and accessible to Inuit patients and the healthcare providers working with them. Not only are we helping to educate and empower Inuit patients and their families, but also better educating healthcare providers around the importance of cultural knowledge in cancer care. Our ultimate goal is to improve health outcomes by increasing awareness and understanding of cancer among Inuit communities. This project is a collaboration between Pauktuutit Inuit Women of Canada and the Canadian Cancer Society. It highlights how partnerships with organizations, both big and small, and connected with the community, can have a real impact.